Ebook: easy research for all / Sylvia Nabila Azwa Ambad - Ambad, Sylvia Nabila Azwa (2021)
In this digital age, each of us needs to embrace technology to make our daily lives more manageable and efficient. Furthermore, in this pandemic where our movement is restricted and made it difficult to meet face-to-face, the use of technology as a medium of communication becomes our new normal. The postgraduate research students were having difficulty meeting face to face with their supervisor. Some of them cannot cope with this situation and cause delays in their progress, and the stress level is accelerated. Therefore, to cater for this problem, the author decided to write the eBooks that can be accessed everywhere and anytime. The ebook consists of complete guidelines with examples of writing a research proposal that consists of Chapter 1, Chapter 2 and Chapter 3 in a thesis. The ebook divided into three series according to chapter. These eBooks enhanced the understanding of research students on preparing an effective research proposal. Now, the research students can breathe a sigh of relief with the help of eBooks. As an implication, from the testimonials and author observation, the students can complete their proposal within the time frame and defence their proposal with confidence and passed with flying colours.